Private credit, and house prices in the Eurozone: a single monetary policy with dissonant transmission mechanisms - Vale, S.; Snyder, T. (7th UECE, 2019)
The relevance for financial stability of booms and busts in house prices and private credit has been highlighted by the recent economic and financial crisis, encouraging the discussion on how do the channels of monetary policy work. This paper studies the role of house prices and private credit in the transmission mechanism of the European monetary policy focusing on a panel of 12 Eurozone countries between 2000Q1 and 2017Q4. Considering the heterogeneity that characterized European housing markets, the analysis distinguishes two groups of countries defined by their average housing inflation up to the financial crisis, besides isolating the period that follows 2008 to capture the impact of the economic turmoil. Using panel vector auto-regression models and impulse response analysis, the estimations indicate nominal money having an asymmetric impact across the Eurozone, being better adjusted to member countries with lower growth rates of house prices. For the whole period, house prices are more effective than credit as a monetary policy channel suggesting wealth effects from housing on output fluctuations. Furthermore, the transmission mechanism of monetary policy changes from 2008 onwards, moving from housing to credit especially for countries that experienced high inflation in their house prices.